2016
DOI: 10.1002/smtd.201600014
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Dopants in Carbon Nanomaterials: Defects or a New Opportunity?

Abstract: Substitutional N‐doping of carbon nanomaterials refers to the chemical functionalization method that replaces a part of the carbon atoms in fullerene, carbon nanotubes, or graphene by nitrogen. N‐doping has attracted a tremendous amount of research attention for their unique possibilities, spanning from its ability to engineer various physiochemical properties of carbon nanomaterials in a stable manner with different dopant configurations. Many viable configurations of N‐dopants are accompanied by typical stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
119
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(120 citation statements)
references
References 72 publications
(128 reference statements)
1
119
0
Order By: Relevance
“…The ever‐rising demand for fossil fuels and a collateral increase in the concentration of atmospheric CO 2 have urged the development of carbon‐management technologies . To this end, much research has been devoted to searching for new technologies for the reduction of CO 2 , for example biological conversion, electrocatalysis, photocatalysis, and photothermal catalysis .…”
Section: Application Of Direct Z‐scheme Photocatalystsmentioning
confidence: 99%
“…The ever‐rising demand for fossil fuels and a collateral increase in the concentration of atmospheric CO 2 have urged the development of carbon‐management technologies . To this end, much research has been devoted to searching for new technologies for the reduction of CO 2 , for example biological conversion, electrocatalysis, photocatalysis, and photothermal catalysis .…”
Section: Application Of Direct Z‐scheme Photocatalystsmentioning
confidence: 99%
“…), metal heteroatoms such as irons can also be introduced into the system . From previous theoretical and practical analyses, it has been confirmed that the inherent characteristics of the heteroatom‐doped carbon materials, including microstructures, compositions, electronic features, and surface and partial activities, would be modified via the collaborations of the doped heteroatoms, leading to lower energy barrier to enhance the reaction activities and electrochemical kinetics in electrochemical devices . Additionally, the electrical conductivity of carbon materials would be further improved by the heteroatom dopants from several to hundreds of S cm −1 , which rely on the types and contents of the heteroatoms and the pyrolysis temperature .…”
Section: Introductionmentioning
confidence: 95%
“…[24] Nitrogen functionalities are able to strengthen the interaction between carbon material surface and reactant molecules. Recently, nitrogen doped porous carbon material supported catalysts have attracted particular interest to researchers.…”
Section: Introductionmentioning
confidence: 99%